ANALISIS KUAT TEKAN BETON MENGGUNAKAN LIMBAH BATU BATA SEBAGAI PENGGANTI SEBAGIAN AGREGAT KASAR - indriasari Koesno; Galih Pribadi; Tomy Friendo Purba (Jurnal Sipil Krisna, 2022)
In a construction project, unused bricks often become waste. This waste has accumulated, which disturbs mobilityand aesthetics at the project site. To reduce this waste, a solution that can be done is to reuse the remaining bricksas other environmentally friendly construction materials. Waste brick can be recycled to be developed in themanufacture of concrete. The choice of brick waste as a concrete mixture is due to its hard structure and similarto natural aggregates. The use of brick waste as a substitute for some coarse aggregate in concrete is expected toreduce the use of natural rock. The purpose of this study was to analyze the comparison of the results of thecompressive strength of concrete in normal concrete and concrete using brick waste. The author conducted thisresearch by comparing the results of compressive strength of normal quality fc '25 concrete with concrete usingbrick waste as much as 5% and 10% as a substitute for coarse aggregate. From the results of this study, thecompressive strength of concrete with brick waste as much as 5% is 25.78 Mpa and with the use of brick waste asmuch as 10%, the compressive strength of concrete is 22.02 MPa which is smaller than the compressive strengthof normal concrete which is equal to 29.02 Mpa. From these results it can be seen that there is a decrease in thecompressive strength of concrete against normal concrete at the age of 28 days using 5% brick waste is 11.16%and with 10% brick waste a decrease of 24.12%